Impact of organic manure and combination of N P K S, on yield, fruit quality and fruit mineral content of Khenazi date palm (Phoenix dactylifera L.) cultivar: - - Elsadig, Elsadig Hassan; Aljuburi, Hameed Jasim; Elamin, Ali Hamad Bashir; Gafar, Mohamed Osman (Journal of Scientific Agriculture, 2017)
This study was carried out during three successive seasons 2011, 2012 and 2013 at a private orchard located in Al- Hello in Ajman Emirate (UAE). The experiment was designed to study the effect of organic manure and NPKS as soil application on yield, fruit quality, and fruit mineral nutrient content of Khenazi date palm cultivar grown in sandy soil. Fertilization treatments consisted of N1, 600g or N2, 1000g (urea 46%N), P 800g (triple superphosphate, 48% P2O5), K 1200g (potassium sulphate, 50% K2SO4) and S 700g sulphur (90% granular S), in addition to organic manure. Al experimental trees received 100g mixture of micronutrients, with the exception of the control. The results showed that combination treatments and organic manure significantly affected fruit weight, flesh weight, fruit volume, moisture content and fruit TSS. Application of different fertilization treatments significantly affected yield components of fruit, number of fruits/strand, fruit number/bunch, fruit set percent and total fruit yield / palm. The study revealed that combination of fertilizers improved fruit nutrient content of N, P, K, Ca, Mg, Fe, Zn, Mn and Cu. Moisture and TSS% content, number of fruits/strand, number of fruits/bunch, fruit nutrients content of Fe, Mn and Zn were significantly different due to the application of N1+K+S.